Multi-storey structures with seismic isolation at storey-levels - Phocas, Marios; Pamboris, George (My University, 2017)
Through increasing international research and application activities in the last years, seismic isolation has proven to be an innovative passive control technique in the area of performance-based design of buildings. Seismic isolation is principally based on the incorporation of flexible isolators at the base of low-rise buildings in order to shift the fundamental period outside of the dangerous for resonance, range of periods. In extending the concept of base isolation, the present contribution refers to the control of multi-storey structures under earthquake actions by means of introducing seismic isolation at different elevations of the structure. Thus, the structural response is influenced decisively by the vertically distributed seismic isolation, which at the respective storey-levels is alone capable of controlling the partial and overall stiffness, the force transmission and the energy dissipation process of the respective dynamic adaptable system. During strong earthquakes the effectiveness of the system in further enlarging the period of the building, compared to the classical method of seismic isolation at a unique level, is achieved, most often with decreased inter-storey deflections, and without introducing extensive displacements at the building base, which are often limited by practical constraints. The effectiveness of the proposed control system is investigated in parametric studies, in the time-history range, for a 6-storey building under ten selected earthquakes of the Greek-Mediterranean region, scaled to a maximum ground acceleration of 0.25 g. Most effective vertical distribution of seismic isolation at various storey-levels is proposed, based on the earthquake, structural and isolation characteristics used in the numerical study.
Keywords: Structural control; Seismic isolation; Seismic performance